Molecular Interactions in Binary Mixture of Propylamine with Non-polar Solvents - Gupta, Deepti; Chaudhary, Subhash; Srivastava, Pankaj; Kumar, Dheeraj (Asian Journal of Chemistry, 2010)
Ultrasonic velocity and density measurements for binary mixture: I. propylamine + benzene II. propylamine + toluene III. propylamine + o-xylene at 301.15 K have been utilized to compute excess adiabatic compressibility, excess molar volume, free length and available volume. These values are reported as a function of mole fraction X1 of propylamine βsE vs. X1 and VmE vs. X1 plots are explained in terms of dipoledipole interactions between two like and unlike molecules.